PENGARUH TEMAN SEBAYA TERHADAP PRESTASI BELAJAR SISWA KELAS VIII AL QUR’AN DI MTs AL- HIDAYAH PURWOKERTO - Melina Putri (ISLAMISCHE BILDUNG: Jurnal Pendidikan Agama Islam, 2025)
This study aims to determine the influence of peers on the learning achievement of class VIII Al-Qur'an students at MTs Al-Hidayah Purwokerto. Peers are individuals who have the same position, age, status and mindset. A student will be more open to their peers, they feel comfortable telling everything about themselves. The influence of peers is very important for students because one of the shapers of student character and behavior comes from their friends. If a student has a friend who has a positive attitude in carrying out the commands of Allah SWT or vice versa if the student has a friend with a bad attitude then over time he will unconsciously follow the behavior of his friend so be careful in choosing friends. This study uses a qualitative method with a case study approach. Data collection techniques are carried out through in-depth interviews, participatory observation, and documentation studies. The research informants consisted of 10 class VIII Al-Qur'an students who were selected using purposive sampling techniques. The results of the study showed that peers have a significant influence on student learning achievement through several aspects, namely: learning motivation, discipline, formation of learning habits, and provision of social-emotional support. Students who socialize with peers who have a positive academic orientation tend to show better academic achievement. This study provides important implications for schools to facilitate the formation of positive peer groups in improving student academic achievement.